2015
DOI: 10.1155/2016/4937689
|View full text |Cite
|
Sign up to set email alerts
|

Neurosphere Based Differentiation of Human iPSC Improves Astrocyte Differentiation

Abstract: Neural progenitor cells (NPCs) derived from human induced pluripotent stem cells (iPSCs) are traditionally maintained and proliferated utilizing two-dimensional (2D) adherent monolayer culture systems. However, NPCs cultured using this system hardly reflect the intrinsic spatial development of brain tissue. In this study, we determined that culturing iPSC-derived NPCs as three-dimensional (3D) floating neurospheres resulted in increased expression of the neural progenitor cell (NPC) markers, PAX6 and NESTIN. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…Interestingly, serious attempts have been made to study the employment and the differences between 2D or 3D cultures 28,29 . Zhou et al demonstrated that culturing induced pluripotent stem cells (iPSCs) in 3D conditions resulted in higher expression of both neural progenitor (Pax6 and NESTIN) and astrocyte (GFAP and AQP4) markers as well as yielding a more homogenous cell population compared to those iPSCs cultured in 2D fashion 30 . Recently, András Dinnyés's team reported that iPSCs neural induction in 3D produced a higher number of neural progenitor cells and neurons with longer neurites 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serious attempts have been made to study the employment and the differences between 2D or 3D cultures 28,29 . Zhou et al demonstrated that culturing induced pluripotent stem cells (iPSCs) in 3D conditions resulted in higher expression of both neural progenitor (Pax6 and NESTIN) and astrocyte (GFAP and AQP4) markers as well as yielding a more homogenous cell population compared to those iPSCs cultured in 2D fashion 30 . Recently, András Dinnyés's team reported that iPSCs neural induction in 3D produced a higher number of neural progenitor cells and neurons with longer neurites 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The generation of cell types such as EBs, neural rosettes, and NPCs mimics various stages of in utero neurogenesis 21 . Few protocols also generated unconventional cell types such as EZ spheres 202 or neurospheres 205 . Such alternatives aim to eliminate laborious differentiation steps involving EB formation and manual picking of rosettes.…”
Section: Generating Relevant Neuronal Cell Types For Pdmentioning
confidence: 99%
“…Initially generated using rodent embryonic stem cells (Eiraku et al, ), recent advancements in human stem cell culture have enabled the generation of 3D organoids from pluripotent human embryonic stem cells, multipotent somatic stem cells, and induced‐pluripotent stem cells (iPSCs) allowing expansion directly from patient tissue (Lancaster et al, ). In addition, strategies for reprogramming iPS cells into all major cell types of the nervous system including neurons (Hunsberger et al, ), oligodendrocytes (Prasad et al, ), astrocytes (Jiang et al, ; Zhou et al, ), and microglia (Muffat et al, ) have been developed providing an invaluable resource for studying human neurological disease. Using these techniques, protocols for the generation of human brain‐like cerebral (Lancaster et al, ), cerebellar (Muguruma, Nishiyama, Kawakami, Hashimoto, & Sasai, ), forebrain (Qian et al, ), and mid‐brain (Jo et al, ; Monzel et al, ) organoids have been reported.…”
Section: Cutting Edge Technologies To Understand Glial Function Cellmentioning
confidence: 99%